Psychopathology in Entrepreneurship in Medan, North Sumatra - Rianda Elvinawanty; Soemarco Chaiyadi; Firda Amelia; Khairunnisa (Kusuma Negara Business School, 2020)
Entrepreneurs in conducting their business can experience failures that can occur at any time. As a result of the failure of entrepreneurship is very diverse, such as stress, depression, and experiencing mental stress. This research aimed to explain the psychopathological picture of failed entrepreneurs. This research used qualitative research methods and the sampling technique used is purposive sampling technique. Data obtained through interview and observation methods. The reason researchers used this research technique was to find more about psychopathological aspects of failed entrepreneurs. The results showed that entrepreneurship psychopathology has a significant role in determining success and failure in entrepreneurship. Of all the subjects, the sense of distrust is the aspect that has the most significant role.